Lessons Learned from the MAUDE Database on Transvaginal Synthetic Mesh and Sling Reports. Issue 2 (March 2017) - Abraham, Annie; Tzartzeva, Kristina; Christie, Alana; Zimmern, Philippe
ABSTRACT : Introduction: : We investigated the volume and sources of MDRs (medical device reports) on transvaginal mesh and sling complications in the FDA (Food and Drug Administration) MAUDE (Manufacturer and User Facility Device Experience) database. Methods: : We extracted and analyzed reports on transvaginal mesh and sling complications submitted to the MAUDE database from 2008 to 2014. We also examined reports for major mesh and sling brands as well as reporter occupation. Results: : The number of reports on transvaginal mesh and sling implants increased slowly from 2008 to 2011, ending with 1, 687 reports in 2011. In 2012 the volume increased nearly sevenfold, yielding 11, 710 reports. The year 2013 witnessed an even greater surge, with a total of 43, 680 complication reports. This trend quickly subsided in 2014 as the number of reports decreased to 5, 467. Meanwhile, the number of attorney submitted reports greatly increased by a factor of 18.6 in 2012 and then by a smaller increment in 2013. Physician submitted reports increased threefold in 2012 and then by a factor of 5.6 in 2013. Unfortunately more than half of the 2013 reports list an unknown occupation for the reporter. Conclusions: : The marked growth of transvaginal mesh and sling reports in the MAUDE database, as well as attorney submitted reports, correlated with the timing of the 2011 FDA issued notification warning the public about the risk of complications associated with transvaginal mesh placement. Despite some shortcomings, the MAUDE database offers an appropriate tool to measure overall trends of device complications and serves as a vehicle for the FDA to alert the public regarding potential dangers.